Making a National Vatan in Turkey: Geography Education in the Late Ottoman and Early Republican Periods - ÖZKAN, BEHLÜL (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2014)
The concept of homeland, vatan, the essential part of the nation-state establishing the link between the people and the territory, territorializes the national identity by creating a sense of belonging to the sacred soil and turning the imagined boundaries into physical ones. In Turkey, constructing the borders of the national identity and vatan required the transformation of the Ottoman imperial paradigm into a nation-state. Republican reforms were unprecedented in terms of combining Turkish identity with territoriality. With the establishment of the Turkish nation-state, a sense of nationalism substituted servitude to the sultan with loyalty to vatan. This was revolutionary in that the nation was disassociated from Islam and God as the community of believers and from the Ottoman sultan as his loyal servants and now was anchored to the life-giving vatan. This article examines the change in the pedagogy of space in Turkey from the late nineteenth century to the first three decades of the twentieth century, exploring how the mental maps of Turkish people shifted from an imperial to a national scope.